Multi-stage pickling and impurity removal method for coal-based hard carbon precursor for sodium storage
Through multi-stage pickling and impurity removal methods, in response to inorganic impurities in coal-based materials, the mixed acid secondary and mono-acid three-stage pickling methods are adopted to solve the problem of difficult impurities removal in the prior art, and efficient ash removal and purification are achieved , which improves the sodium storage capacity and battery energy density of hard carbon materials of coal-based sodium ion batteries.
Patent Information
- Application Number
- CN202411658800.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The prior art is difficult to effectively remove minerals and non-combustible impurities in coal-based materials, resulting in high ash content, trace metal elements and magnetic substances of hard carbon materials, affecting their sodium storage capacity and battery energy density.
Multi-stage pickling and impurity removal methods are adopted, including mixed acid secondary pickling and impurity removal methods and mono-acid three-stage pickling and impurity removal methods. Through the combination and sequence of different pickling solutions, the inorganic impurities in coal-based materials can be efficiently removed and reduced. Content of ash and trace metal elements.
It has achieved efficient ash removal and purification, and prepared high-quality coal-based sodium ion battery hard carbon material with low ash, which has improved its sodium storage capacity and battery energy density. The charging specific capacity of the first circle reaches 291.21 mAh/g, and the efficiency of the first circle of Kulun is achieved. 92.52%.
Smart Images

Figure CN119160877B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a multi-stage acid washing and impurity removal method for a coal-based hard carbon precursor for sodium storage. Background Art
[0002] Sodium-ion batteries are a promising new low-cost energy storage technology in the post-lithium-ion era, showing good application potential in low-speed electric vehicles, large-scale energy storage, power tools, and smart homes. The rapid development of sodium-ion battery energy storage technology can alleviate the excessive dependence on lithium resources to a certain extent. However, due to the limitations of the battery's positive and negative electrode material systems, the energy density of sodium-ion batteries is usually lower than that of lithium-ion batteries, so the development of high-performance electrode materials is of great significance to improving the energy density of sodium-ion batteries. The negative electrode material is a necessary component of the sodium-ion battery, and its platform voltage and specific capacity directly determine the energy density of the sodium-ion full battery.
[0003] Among the many types of sodium storage negative electrode materials, hard carbon materials have the characteristics of low cost, low platform voltage and high sodium storage capacity, and are one of the ideal choices for sodium ion battery negative electrodes. Hard carbon materials refer to carbon that is difficult to graphitize at high temperatures (2000~2500°C), and its carbon structure exhibits the characteristics of long-range disorder and short-range order. Hard carbon material precursors mainly include fruit shells (coconut shells, apricot shells, walnut shells, etc.), coal-based materials (bituminous coal, anthracite, lignite) and resins. Among them, the hard carbon material precursor with relatively low raw material cost belongs to coal-based materials.
[0004] The components of coal-based materials (coal) mainly include complex high-molecular organic mixtures (composed of elements such as carbon, hydrogen, oxygen, nitrogen, sulfur and phosphorus), minerals (composed of inorganic salts such as calcium, iron, aluminum, magnesium, sulfur, zinc, cobalt, nickel, copper, silicon, etc.) and water. As a precursor of hard carbon materials, the ash content of coal-based materials mainly comes from a large amount of minerals. The high ash content causes the presence of impurities such as metal oxides, aluminosilicates and carbonates in the product of the hard carbon material precursor (coal-based hard carbon); at the same time, transition metal impurities such as iron, cobalt, nickel and copper will catalyze the formation of graphitized carbon in coal-based hard carbon during the high-temperature carbonization process, which ultimately leads to a decrease in the sodium storage active sites in the carbon structure. In addition, the sodium storage capacity of graphitized carbon is low, which ultimately leads to poor sodium storage capacity of hard carbon materials. Therefore, effectively removing minerals and non-combustible impurities in coal-based materials to reduce the ash, trace elements and magnetic material content of coal-based materials is an important prerequisite for constructing low-cost and high-performance hard carbon materials for sodium storage (the cyclic stability of coal-based hard carbon is generally good, but its first-cycle coulombic efficiency and first-cycle charge specific capacity are low, which leads to a decrease in the energy density of sodium-ion full batteries, making it difficult to be widely used.).
[0005] Common impurity removal processes for coal-based materials mainly include physical methods and chemical methods. The physical method is mainly a multi-stage flotation method. For example, the Chinese patent with publication number CN118026143A discloses a method for preparing batteries using a physical-chemical combined deashing method for coal. This method uses high-speed shearing and then multi-stage flotation tests to perform physical impurity removal and deashing. The chemical method is mainly acid washing or alkaline washing for impurity removal and deashing. The patent application with publication number CN115650228A discloses a method and application for preparing coal-based hard carbon negative electrode materials by alkaline treatment modification, wherein the acid washing impurity removal step is a single-stage acid washing using one or more of hydrochloric acid, nitric acid, sulfuric acid and hydrofluoric acid. The patent application with publication number CN116654893A discloses a flexible control method and application for a lignite-based power / capacity sodium-ion battery hard carbon negative electrode, wherein the acid washing and deashing treatment procedure is a hydrochloric acid / hydrofluoric acid mixed acid treatment. The patent with publication number CN117776153A discloses a method for preparing coal-coke-based hard carbon by solvent thermal assisted low-temperature heat treatment, wherein the pickling and impurity removal process is to use hydrochloric acid and hydrofluoric acid together or use them successively. The patent application with publication number CN118062827A discloses a method for preparing a bituminous coal-based hard carbon material by pre-pore formation combined with high-temperature carbonization, wherein the impurity removal pretreatment method is to wash with hydrochloric acid first and then with sodium hydroxide.
[0006] In the method adopted in the above patent, it is difficult to completely wash the elements such as calcium, iron, aluminum, magnesium, sulfur, zinc, cobalt, nickel, copper, silicon and phosphorus by single-stage washing with single acid (hydrochloric acid, nitric acid, hydrofluoric acid). Among them, it is difficult to remove substances such as silicates or aluminosilicates by single-stage washing with hydrochloric acid or nitric acid. Although washing with hydrofluoric acid can remove most elements such as iron, aluminum, magnesium, cobalt, nickel and silicon, fluoride ions will coordinate with calcium ions to form insoluble calcium fluoride.
[0007] In the patent publication number CN117776153A, the two-stage pickling with hydrochloric acid followed by hydrofluoric acid can theoretically remove most impurity elements including calcium, but the first step of hydrochloric acid washing is difficult to completely remove calcium ions, resulting in the formation of calcium fluoride precipitation in the second step of hydrofluoric acid washing. The single-stage washing with mixed acid of hydrochloric acid / hydrofluoric acid or nitric acid / hydrofluoric acid is also difficult to avoid the formation of calcium fluoride.
[0008] In summary, there is an urgent need in this field to develop a multi-stage acid washing and impurity removal method for coal-based hard carbon precursors for sodium storage, so as to reduce the ash content, trace metal elements and magnetic substances in coal-based materials (coal-based hard carbon precursors), thereby improving the application value of coal-based hard carbon precursors. Summary of the invention
[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide a multi-stage acid washing and impurity removal method for a coal-based hard carbon precursor for sodium storage.
[0010] The purpose of the present invention is achieved through the following technical solutions.
[0011] A multi-stage pickling and impurity removal method for a coal-based hard carbon precursor for sodium storage comprises the following steps:
[0012] S1, pickling and removing impurities from coal-based material powder according to a mixed acid secondary pickling and removing impurities method or a single acid tertiary pickling and removing impurities method to obtain pickled coal-based material powder, wherein:
[0013] The mixed acid two-stage pickling and impurity removal method comprises: using hydrochloric acid-hydrofluoric acid or nitric acid-hydrofluoric acid as a pickling solution for pickling once, and then using nitric acid-aluminum nitrate as a pickling solution for pickling once;
[0014] The single-acid three-stage pickling and impurity removal method is: using nitric acid as a pickling liquid to carry out pickling once, then using hydrochloric acid as a pickling liquid to carry out pickling once, and finally using hydrofluoric acid as a pickling liquid to carry out pickling once;
[0015] The hydrochloric acid-hydrofluoric acid is a mixture of hydrochloric acid and hydrofluoric acid, the concentration of HCl in the hydrochloric acid-hydrofluoric acid is 0.1-6 mol / L, preferably 5-6 mol / L; the concentration of HF in the hydrochloric acid-hydrofluoric acid is 0.1-6 mol / L, preferably 5-6 mol / L; the nitric acid-hydrofluoric acid is a mixture of nitric acid and hydrofluoric acid, the concentration of HNO3 in the nitric acid-hydrofluoric acid is 0.1-6 mol / L, preferably 5-6 mol / L; the concentration of HF in the nitric acid-hydrofluoric acid is 0.1-6 mol / L, preferably 5-6 mol / L; the nitric acid-nitroaluminic acid is a mixture of nitric acid and aluminum nitrate, the concentration of HNO3 in the nitric acid-aluminum nitrate is 0.1-6 mol / L, preferably 0.1-1 mol / L; the concentration of aluminum nitrate in the nitric acid-aluminum nitrate is 0.1-12 mol / L, preferably 0.1-0.2 mol / L;
[0016] The concentration of HNO3 in nitric acid in the single-acid three-stage pickling and impurity removal method is 0.1~6 mol / L (preferably 5~6 mol / L), the concentration of HCl in hydrochloric acid in the single-acid three-stage pickling and impurity removal method is 0.1~6 mol / L (preferably 5~6 mol / L), and the concentration of HF in hydrofluoric acid in the single-acid three-stage pickling and impurity removal method is 0.1~6 mol / L (preferably 5~6 mol / L);
[0017] Each pickling comprises: dispersing the solid to be pickled in the pickling solution and stirring for at least 6 hours, standing for 2 to 12 hours, filtering, washing to neutrality, and drying.
[0018] In the S1, the particle size of the coal-based material powder is 2-10 μm.
[0019] In S1, the method for obtaining coal-based material powder includes: coarsely crushing, ball milling, and sieving the coal-based material to obtain the coal-based material powder, wherein the coal-based material is a coal-based hard carbon precursor for sodium storage.
[0020] In S1, each time pickling is performed, the ratio of the mass fraction of the solid to be pickled to the volume fraction of the pickling liquid is 1:(1-3), the unit of the mass fraction is g, and the unit of the volume fraction is mL.
[0021] In S1, the drying temperature is 80-120° C., and the drying time is at least 6 hours.
[0022] In S1, the stirring time is 6 to 24 hours.
[0023] S2, in an inert atmosphere, sintering the acid-washed coal-based material powder at 500-800°C for 0-4h, then carbonizing at 800-1450°C for 0.5-18h, and cooling to room temperature to obtain a coal-based sodium ion battery hard carbon material.
[0024] In S2, the inert atmosphere is one or more of an argon atmosphere, a nitrogen atmosphere and a helium atmosphere.
[0025] In S2, the temperature is increased to 500-800°C at a rate of 1-5°C / min.
[0026] In S2, the temperature is increased to 800-1450°C at a rate of 1-5°C / min.
[0027] In the step S2, cooling to room temperature comprises: firstly cooling to 500-700°C at a rate of 1-10°C / min, and then cooling to room temperature in the furnace.
[0028] An alkaline ion battery comprises: a coal-based sodium ion battery hard carbon material obtained by a multi-stage acid washing and impurity removal method.
[0029] In the above technical solution, the alkaline ion battery is a sodium ion battery, a lithium ion battery or a potassium ion battery.
[0030] In the above technical solution, the first-cycle charging specific capacity of the sodium-ion battery is 270~300mAh / g, the first-cycle discharge specific capacity is 300~320mAh / g, and the first-cycle Coulomb efficiency is greater than 90%.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The multi-stage pickling and impurity removal method of the present invention sets the pickling sequence according to the types and existence forms of inorganic elements in the coal-based material (i.e., the coal-based hard carbon precursor for sodium storage), and proposes an efficient multi-stage pickling method (a single acid three-stage pickling and impurity removal method and a mixed acid two-stage pickling and impurity removal method) to remove inorganic impurities in the coal-based material, thereby achieving the effect of efficient ash removal and purification, thereby preparing high-quality low-ash coal-based hard carbon materials for sodium ion batteries. Therefore, the multi-stage pickling and impurity removal method of the present invention can effectively remove minerals and non-combustible impurities in coal, thereby reducing the ash content, trace metal elements and magnetic material content of the coal-based material, and is low-cost, which is of great significance for the large-scale preparation of high-performance hard carbon materials for sodium storage.
[0033] (2) The coal-based sodium ion battery hard carbon material obtained by the present invention has the advantages of high capacity and high first efficiency, and exhibits excellent sodium storage performance. The first cycle charging specific capacity of the coal-based sodium ion battery hard carbon material can reach up to 291.21 mAh / g, and the first efficiency (first cycle coulomb efficiency) can reach 92.52%. At the same time, the trace metal elements and magnetic substances in the coal-based sodium ion battery hard carbon material meet the national standards for sodium ion battery hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 are X-ray diffraction (XRD) diagrams, (a) is the ash product of the coal-based hard carbon material obtained in Comparative Example 6 and the acid-washed coal-based material powder obtained by S1, (b) is the coal-based sodium ion battery hard carbon material obtained in Example 1 and the acid-washed coal-based material powder obtained by S1, and (c) is the coal-based sodium ion battery hard carbon material obtained in Example 2 and the acid-washed coal-based material powder obtained by S1;
[0035] Figure 2 The first cycle charge and discharge test diagram of CR2032 button batteries prepared from the coal-based sodium ion battery hard carbon material obtained in Example 1 and the coal-based hard carbon material obtained in Comparative Examples 2-3;
[0036] Figure 3 The first cycle charge and discharge test diagram of CR2032 button batteries prepared from the coal-based sodium ion battery hard carbon material obtained in Example 2, and the coal-based hard carbon materials obtained in Comparative Example 1 and Comparative Examples 6-7;
[0037] Figure 4 This is a test chart of the first cycle of charge and discharge of a CR2032 button-type battery prepared from the coal-based sodium ion battery hard carbon material obtained in Example 3. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0039] In the following examples, the reagents, materials and instruments used are conventional reagents, conventional materials and conventional instruments unless otherwise specified, and can be obtained commercially.
[0040] In the following embodiments, the concentration of HNO3 in nitric acid in the single-acid three-stage pickling and impurity removal method is 5 mol / L, the concentration of HCl in hydrochloric acid in the single-acid three-stage pickling and impurity removal method is 5 mol / L, and the concentration of HF in hydrofluoric acid in the single-acid three-stage pickling and impurity removal method is 5 mol / L.
[0041] In the following examples, hydrochloric acid-hydrofluoric acid is a mixture of hydrochloric acid and hydrofluoric acid, the concentration of HCl in the hydrochloric acid-hydrofluoric acid is 5 mol / L, and the concentration of HF in the hydrochloric acid-hydrofluoric acid is 5 mol / L.
[0042] In the following examples, nitric acid-hydrofluoric acid is a mixture of nitric acid and hydrofluoric acid, the concentration of HNO3 in the nitric acid-hydrofluoric acid is 5 mol / L, and the concentration of HF in the nitric acid-hydrofluoric acid is 5 mol / L.
[0043] In the following examples, nitric acid-aluminum nitrate is a mixture of nitric acid and aluminum nitrate, the concentration of HNO3 in nitric acid-aluminum nitrate is 1 mol / L, and the concentration of aluminum nitrate in nitric acid-aluminum nitrate is 0.2 mol / L.
[0044] In the following embodiments, a method for preparing a coal-based hard carbon electrode sheet is as follows: a hard carbon material, a sodium carboxymethyl cellulose solution, a carbon nanotube and a styrene-butadiene rubber solution are uniformly mixed and stirred for 12 hours to obtain a slurry, the slurry is uniformly coated on a copper foil using a scraper, and the slurry is placed in a drying oven at 100°C for 6 hours. The dried copper foil is rolled and punched into a disc with a diameter of 12 mm as a coal-based hard carbon electrode sheet, wherein the hard carbon material is one of the coal-based sodium ion battery hard carbon materials obtained in the following embodiments 1 to 5 and the coal-based hard carbon materials obtained in comparative examples 1 to 8, the sodium carboxymethyl cellulose solution is a mixture of sodium carboxymethyl cellulose and water, and the concentration of sodium carboxymethyl cellulose in the sodium carboxymethyl cellulose solution is 1wt%, the styrene-butadiene rubber solution is a mixture of styrene-butadiene rubber and water, and the concentration of styrene-butadiene rubber in the styrene-butadiene rubber solution is 40wt%, and the ratio of the hard carbon material, the sodium carboxymethyl cellulose in the sodium carboxymethyl cellulose solution, the carbon nanotube and the styrene-butadiene rubber in the styrene-butadiene rubber solution is 92.5:1.5:3:3 by mass.
[0045] In the following embodiments, a method for assembling a CR 2032 button battery is provided: a coal-based hard carbon electrode sheet is used as a working electrode, a metal sodium sheet is used as a counter electrode, a Whatman glass fiber membrane is used as a diaphragm, and the electrolyte is a 1M NaPF6-DIGLYME electrolyte; the battery is packaged in a glove box (the content of O2 and H2O is less than 0.01 ppm) to obtain a CR 2032 button battery, wherein the hard carbon material of the coal-based hard carbon electrode sheet is one of the coal-based sodium ion battery hard carbon materials obtained in Examples 1 to 5 and the coal-based hard carbon materials obtained in Comparative Examples 1 to 8; the NaPF6-DIGLYME electrolyte comprises sodium hexafluorophosphate (NaPF6) and diethylene glycol dimethyl ether (DIGLYME); and the concentration of sodium hexafluorophosphate (NaPF6) in the NaPF6-DIGLYME electrolyte is 1 mol / L.
[0046] In the following examples, a CR 2032 button cell was subjected to a first cycle charge and discharge test on a blue battery tester, and the test conditions were: at a current density of 0.1C, discharged to 0.005 V, and then charged to 2 V, where 1 C = 300 mA / g.
[0047] In the following embodiments, a method for obtaining coal-based material powder comprises: coarsely crushing the coal-based material, high-energy ball milling at a rotation speed of 1300 rpm for 3 minutes after the coarse crushing, and passing through a 1500 mesh sieve to obtain a coal-based material powder with a particle size of about 5 μm, wherein the coal-based material is a coal-based hard carbon precursor for sodium storage, and the coal-based hard carbon precursor for sodium storage is Xinjiang coal.
[0048] In the following embodiments, each pickling includes: dispersing the solid to be pickled (coal-based material powder or the solid obtained after the previous pickling) in the pickling liquid and stirring for 6 hours, standing for 6 hours, filtering, washing to neutrality, and drying at 80°C for 6 hours. The mass fraction of the solid to be pickled and the volume fraction of the pickling liquid are 1:2, the unit of mass fraction is g, and the unit of volume fraction is mL. Example 1
[0049] A multi-stage pickling and impurity removal method for a coal-based hard carbon precursor for sodium storage comprises the following steps:
[0050] S1, pickling and removing impurities from coal-based material powder according to a single-acid three-stage pickling and impurity removal method to obtain pickled coal-based material powder, wherein the single-acid three-stage pickling and impurity removal method is: using nitric acid as a pickling liquid to perform pickling once, then using hydrochloric acid as a pickling liquid to perform pickling once, and finally using hydrofluoric acid as a pickling liquid to perform pickling once.
[0051] S2, under argon atmosphere, the acid-washed coal-based material powder is placed in a tubular furnace, the temperature is increased to 500°C at a rate of 3°C / min and sintered at 500°C for 2h, then the temperature is increased to 1400°C at a rate of 3°C / min and high-temperature carbonized at 1400°C for 4h, after high-temperature carbonization, the temperature is decreased to 600°C at a rate of 5°C / min, and then cooled to room temperature with the furnace to obtain a coal-based sodium ion battery hard carbon material. Example 2
[0052] A multi-stage pickling and impurity removal method for a coal-based hard carbon precursor for sodium storage is basically the same as Example 1, with the only difference being S1: S1 in Example 2 pickles and removes impurities from the coal-based material powder according to a mixed acid secondary pickling and impurity removal method to obtain a pickled coal-based material powder, wherein the mixed acid secondary pickling and impurity removal method is: using hydrochloric acid-hydrofluoric acid as the pickling solution for one pickling, and then using nitric acid-aluminum nitrate as the pickling solution for one pickling. Example 3
[0053] A multi-stage acid washing and impurity removal method for a coal-based hard carbon precursor for sodium storage is basically the same as Example 2, with the only difference being S2: S2 in Example 3 is to place the acid-washed coal-based material powder in a tubular furnace under an argon atmosphere, heat the temperature to 1300°C at a rate of 2.5°C / min and carbonize at 1300°C for 2 h, then cool the temperature to 500°C at a rate of 2.5°C / min after high-temperature carbonization, and then cool to room temperature with the furnace to obtain a coal-based sodium ion battery hard carbon material. Example 4
[0054] A multi-stage pickling and impurity removal method for a coal-based hard carbon precursor for sodium storage is basically the same as Example 2, with the only difference being S1: S1 in Example 4 pickles and removes impurities from the coal-based material powder according to a mixed acid secondary pickling and impurity removal method to obtain a pickled coal-based material powder, wherein the mixed acid secondary pickling and impurity removal method is: pickling once using nitric acid-hydrofluoric acid as the pickling solution, and then pickling once using nitric acid-aluminum nitrate as the pickling solution. Example 5
[0055] A multi-stage acid washing and impurity removal method for a coal-based hard carbon precursor for sodium storage is basically the same as Example 4, with the only difference being S2: S2 of Example 5 is to place the acid-washed coal-based material powder in a tubular furnace under an argon atmosphere, heat the temperature to 1300°C at a heating rate of 2.5°C / min and carbonize at 1300°C for 2 h, then reduce the temperature to 500°C at a rate of 2.5°C / min after high-temperature carbonization, and then cool the furnace to room temperature to obtain a coal-based sodium ion battery hard carbon material. Comparative Example 1
[0056] A method for preparing a coal-based hard carbon material comprises the following steps:
[0057] Under argon atmosphere, the coal-based material powder (unacid washed) was placed in a tubular furnace, heated to 500°C at a rate of 3°C / min and sintered at 500°C for 2h, then heated to 1400°C at a rate of 3°C / min and carbonized at 1400°C for 4h. After high-temperature carbonization, the temperature was reduced to 600°C at a rate of 5°C / min and then cooled to room temperature with the furnace to obtain a coal-based hard carbon material. Comparative Example 2
[0058] A method for preparing coal-based hard carbon material by pickling and removing impurities is basically the same as Example 1, with the only difference being S1: In S1 of Comparative Example 2, the coal-based material powder is pickled and removed impurities according to a single-acid primary pickling and removing impurities method to obtain a pickled coal-based material powder, wherein the single-acid primary pickling and removing impurities method is: pickling once using nitric acid as the pickling liquid. Comparative Example 3
[0059] A method for preparing coal-based hard carbon material by pickling and removing impurities is basically the same as Example 1, with the only difference being S1: In S1 of Comparative Example 3, the coal-based material powder is pickled and removed impurities according to the single-acid secondary pickling and removing impurities method to obtain the pickled coal-based material powder, wherein the single-acid secondary pickling and removing impurities method is: pickling once with nitric acid as the pickling liquid, and then pickling once with hydrochloric acid as the pickling liquid. Comparative Example 4
[0060] A method for preparing coal-based hard carbon material by pickling and removing impurities is basically the same as Example 1, with the only difference being S1: In S1 of Comparative Example 4, the coal-based material powder is pickled and removed impurities according to the single-acid secondary pickling and removing impurities method to obtain the pickled coal-based material powder, wherein the single-acid secondary pickling and removing impurities method is: pickling once with nitric acid as the pickling liquid, and then pickling once with hydrofluoric acid as the pickling liquid. Comparative Example 5
[0061] A method for preparing coal-based hard carbon material by pickling and removing impurities is basically the same as Example 1, except that S1: In S1 of Comparative Example 5, the coal-based material powder is pickled and removed impurities according to the single-acid secondary pickling and removing impurities method to obtain the pickled coal-based material powder, wherein the single-acid secondary pickling and removing impurities method is: using hydrochloric acid as the pickling liquid for pickling once, and then using hydrofluoric acid as the pickling liquid for pickling once. Comparative Example 6
[0062] A method for preparing coal-based hard carbon material by pickling and removing impurities is basically the same as Example 1, with the only difference being S1: In S1 of Comparative Example 6, the coal-based material powder is pickled and removed impurities according to a mixed acid primary pickling and removing impurities method to obtain a pickled coal-based material powder, wherein the mixed acid primary pickling and removing impurities method is: using hydrochloric acid-hydrofluoric acid as the pickling liquid for a single pickling. Comparative Example 7
[0063] A method for preparing coal-based hard carbon material by pickling and removing impurities is basically the same as Example 1, with the only difference being S1: In S1 of Comparative Example 7, the coal-based material powder is pickled and removed impurities according to a mixed acid primary pickling and removing impurities method to obtain a pickled coal-based material powder, wherein the mixed acid primary pickling and removing impurities method is: using nitric acid-hydrofluoric acid as the pickling liquid for a single pickling. Comparative Example 8
[0064] A method for preparing coal-based hard carbon material by pickling and removing impurities is basically the same as Example 1, with the only difference being S1: In S1 of Comparative Example 8, the coal-based material powder is pickled and removed impurities according to the single-acid three-stage pickling and removing impurities method to obtain the pickled coal-based material powder, wherein the single-acid three-stage pickling and removing impurities method is: using hydrofluoric acid as the pickling liquid for pickling once, then using hydrochloric acid as the pickling liquid for pickling once, and finally using nitric acid as the pickling liquid for pickling once.
[0065] The pickled coal-based material powder obtained in S1 of Comparative Example 6 and Examples 1-2 were subjected to ash content tests according to the national standard GB / T 214-2017. After the ash content test of the pickled coal-based material powder obtained in S1 of Example 1, the mass of the ash product was less than 0.2% compared with that before the ash content test. After the ash content test of the pickled coal-based material powder obtained in S1 of Example 2, the mass of the ash product was less than 0.1% compared with that before the ash content test, that is, there was almost no ash product. After the ash content test of the pickled coal-based material powder obtained in S1 of Comparative Example 6, a certain mass of ash product was produced, which could be subjected to X-ray diffraction (XRD).
[0066] Figure 1 The X-ray diffraction (XRD) diagrams are shown in Figures 1 and 2. (a) is the ash product of the coal-based hard carbon material obtained in Comparative Example 6 and the acid-washed coal-based material powder obtained in S1, (b) is the coal-based sodium ion battery hard carbon material obtained in Example 1 and the acid-washed coal-based material powder obtained in S1, and (c) is the coal-based sodium ion battery hard carbon material obtained in Example 2 and the acid-washed coal-based material powder obtained in S1. Figure 1 It can be seen that in Comparative Example 6, CaF2 exists in the ash product of the pickled coal-based material powder obtained in S1. The common mixed acid primary pickling and impurity removal method (the pickling liquid is hydrochloric acid-hydrofluoric acid) will lead to the generation of CaF2 impurities in the pickled coal-based material powder; even after the pickled coal-based material powder is carbonized at high temperature under an inert atmosphere, the CaF2 impurities in the coal-based hard carbon material are still difficult to remove. Although hydrochloric acid-hydrofluoric acid can remove calcium ions (Ca 2+ ) and most metal elements except silicon, but Ca 2+ Easy and F - Coordinated deposition leads to the precipitation of CaF2. Similarly, nitric acid-hydrofluoric acid pickling will also lead to the production of CaF2. Therefore, in order to reduce impurities, trace metal elements and magnetic substances to achieve the purpose of reducing ash content and purifying coal samples, a multi-stage pickling process needs to be accurately designed.
[0067] In Example 1 of the present invention, a single acid three-stage pickling method is used to prepare a coal-based sodium ion battery hard carbon material. First, nitric acid is used for pickling, then hydrochloric acid is used for pickling to remove other impurities except Si, and finally hydrofluoric acid is used for pickling to remove Si. In Example 2, a mixed acid two-stage pickling method is used to prepare a coal-based sodium ion battery hard carbon material. First, hydrochloric acid-hydrofluoric acid is used to remove Ca 2+ Other impurities except for the above are then washed with nitric acid-aluminum nitrate to remove the CaF2 impurities produced in the first step (the reaction mechanism for removing CaF2 impurities: Al 3+ + 3CaF2 = 3Ca 2+ + AlF6 3- ).Depend on Figure 1 It can be further seen that there is no CaF2 impurity in the coal-based sodium ion battery hard carbon material obtained in Examples 1 to 2, indicating that the single acid three-stage pickling and impurity removal method and the mixed acid two-stage pickling and impurity removal method can avoid the presence of other crystalline impurities in the pickled coal-based material powder after pickling and impurity removal, confirming the positive effect of the multi-stage pickling and impurity removal method proposed in the present invention.
[0068] The first cycle charge and discharge test was performed on the CR 2032 button batteries prepared using the coal-based sodium ion battery hard carbon materials obtained in Examples 1 to 5 and the coal-based hard carbon materials obtained in Comparative Examples 1 to 8. The test results are shown in Table 1.
[0069] Table 1
[0070]
[0071] Figure 2 The first cycle charge and discharge test diagram of the CR2032 button battery prepared with the coal-based sodium ion battery hard carbon material obtained in Example 1 and the coal-based hard carbon material obtained in Comparative Examples 2-3. The test results are as follows Figure 2 As shown by Figure 2 It can be seen that compared with the coal-based hard carbon materials obtained in Comparative Example 2 using the single-acid primary pickling and impurity removal method and Comparative Example 3 using the single-acid secondary pickling and impurity removal method, the coal-based sodium ion battery hard carbon material obtained in Example 1 using the single-acid three-stage pickling and impurity removal method has the best performance, and the first-cycle charging specific capacity of the CR2032 button battery prepared therefrom is 280.83 mAh / g, and the first-cycle coulomb efficiency (ICE) reaches 90.13%. At the same time, the contents of trace metal elements and magnetic substances in the coal-based sodium ion battery hard carbon material obtained in Example 1 both meet the national standard for hard carbon (GB / T 43114-2023), and the contents of trace metal elements and magnetic substances are shown in Table 2, which further illustrates the positive effect of the single-acid three-stage pickling and impurity removal scheme of the present invention.
[0072] Table 2
[0073]
[0074] Figure 3 The first cycle charge and discharge test diagram of the CR2032 button battery prepared from the coal-based sodium ion battery hard carbon material obtained in Example 2, and the coal-based hard carbon material obtained in Comparative Example 1 and Comparative Examples 6-7. Figure 3 It can be seen that compared with the coal-based hard carbon materials obtained in Comparative Examples 6 to 7 using the mixed acid primary pickling and impurity removal method, the coal-based sodium ion battery hard carbon material obtained in Example 2 using the mixed acid secondary pickling and impurity removal method has the best performance, and the first-cycle charging specific capacity of the CR2032 button battery prepared therefrom is 287.67 mAh / g, and the first-cycle coulomb efficiency reaches 93.00%. At the same time, the contents of trace metal elements and magnetic substances in the coal-based sodium ion battery hard carbon material obtained in Example 2 both meet the national standard for hard carbon (GB / T 43114-2023), and the contents of trace metal elements and magnetic substances are shown in Table 3, which further illustrates that the multi-stage pickling and impurity removal method of the coal-based hard carbon precursor for sodium storage of the present invention has a significant effect, and its pickling effect is better than that of the coal-based sodium ion battery hard carbon material obtained in Example 1. The multi-stage pickling and impurity removal method of the coal-based hard carbon precursor for sodium storage of the present invention can solve the CaF2 precipitation caused by the mixed acid one-stage pickling and impurity removal method (such as hydrochloric acid-hydrofluoric acid pickling or nitric acid-hydrofluoric acid pickling), providing an effective solution.
[0075] Table 3
[0076]
[0077] Figure 4 The first cycle charge and discharge test diagram of the CR2032 button battery prepared from the coal-based sodium ion battery hard carbon material obtained in Example 3. Compared with the coal-based sodium ion battery hard carbon materials obtained in Examples 2 to 5, the mixed acid secondary pickling and impurity removal method can be further optimized by regulating the sintering and high-temperature carbonization temperature, heating rate, and sintering and high-temperature carbonization time, thereby improving the electrochemical properties of the obtained coal-based sodium ion battery hard carbon material. Among them, the coal-based sodium ion battery hard carbon material obtained in Example 3 has the best first-cycle charge specific capacity of 291.21 mAh / g, and the first-cycle coulomb efficiency is 92.52%.
[0078] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A multi-stage pickling and impurity removal method for coal-based hard carbon precursor for sodium storage, characterized in that: The following steps are involved: S1, pickling and removing impurities from coal-based material powder according to a mixed acid secondary pickling and removing impurities method or a single acid tertiary pickling and removing impurities method to obtain pickled coal-based material powder, wherein: The mixed acid two-stage pickling and impurity removal method comprises: using hydrochloric acid-hydrofluoric acid or nitric acid-hydrofluoric acid as a pickling solution for pickling once, and then using nitric acid-aluminum nitrate as a pickling solution for pickling once; first using hydrochloric acid-hydrofluoric acid or nitric acid-hydrofluoric acid to remove Ca 2+ Other impurities other than the above are then pickled with nitric acid-aluminum nitrate to remove the CaF2 impurities produced by the first pickling in the mixed acid secondary pickling and impurity removal method; The single-acid three-stage pickling and impurity removal method is: using nitric acid as a pickling liquid to carry out pickling once, then using hydrochloric acid as a pickling liquid to carry out pickling once, and finally using hydrofluoric acid as a pickling liquid to carry out pickling once; The hydrochloric acid-hydrofluoric acid is a mixture of hydrochloric acid and hydrofluoric acid, the concentration of HCl in the hydrochloric acid-hydrofluoric acid is 0.1-6 mol / L, and the concentration of HF in the hydrochloric acid-hydrofluoric acid is 0.1-6 mol / L; the nitric acid-hydrofluoric acid is a mixture of nitric acid and hydrofluoric acid, the concentration of HNO3 in the nitric acid-hydrofluoric acid is 0.1-6 mol / L, and the concentration of HF in the nitric acid-hydrofluoric acid is 0.1-6 mol / L; nitric acid-nitroaluminic acid is a mixture of nitric acid and aluminum nitrate, the concentration of HNO3 in the nitric acid-aluminum nitrate is 0.1-6 mol / L, and the concentration of aluminum nitrate in the nitric acid-aluminum nitrate is 0.1-12 mol / L; The concentration of HNO3 in nitric acid in the single-acid three-stage pickling and impurity removal method is 0.1~6 mol / L, the concentration of HCl in hydrochloric acid in the single-acid three-stage pickling and impurity removal method is 0.1~6 mol / L, and the concentration of HF in hydrofluoric acid in the single-acid three-stage pickling and impurity removal method is 0.1~6 mol / L; Each pickling process comprises: dispersing the solid to be pickled in the pickling solution, stirring for at least 6 hours, standing for 2 to 12 hours, filtering, washing to neutrality, and drying; S2, in an inert atmosphere, sintering the acid-washed coal-based material powder at 500-800°C for 0-4h, then carbonizing at 800-1450°C for 0.5-18h, and cooling to room temperature to obtain a coal-based sodium ion battery hard carbon material.
2. The multi-stage pickling and impurity removal method according to claim 1, characterized in that: The particle size of coal-based material powder is 2~10μm.
3. The multi-stage pickling and impurity removal method according to claim 1, characterized in that: The method for obtaining coal-based material powder comprises: coarsely crushing, ball-milling and sieving the coal-based material to obtain the coal-based material powder, wherein the coal-based material is a coal-based hard carbon precursor for sodium storage.
4. The multi-stage pickling and impurity removal method according to claim 1, characterized in that: During each pickling, the ratio of the mass fraction of the solid to be pickled to the volume fraction of the pickling solution is 1:(1-3), the unit of the mass fraction is g, and the unit of the volume fraction is mL.
5. The multi-stage pickling and impurity removal method according to claim 1, characterized in that: The drying temperature is 80-120° C., and the drying time is at least 6 hours; in S1, the stirring time is 6-24 hours.
6. The multi-stage pickling and impurity removal method according to claim 1, characterized in that: In S2, the inert atmosphere is one or more of an argon atmosphere, a nitrogen atmosphere and a helium atmosphere.
7. The multi-stage pickling and impurity removal method according to claim 1, characterized in that: Cooling to room temperature includes: firstly cooling to 500-700°C at a rate of 1-10°C / min, and then cooling to room temperature along with the furnace.
8. An alkaline ion battery, characterized in that: include: A coal-based sodium ion battery hard carbon material obtained by the multi-stage pickling and impurity removal method according to any one of claims 1 to 7.
9. The alkali ion battery according to claim 8, characterized in that: Alkaline ion batteries are sodium ion batteries, lithium ion batteries or potassium ion batteries.
10. The alkali ion battery according to claim 9, characterized in that: The first-cycle charge capacity of sodium-ion batteries is 270~300mAh / g, the first-cycle discharge capacity is 300~320mAh / g, and the first-cycle Coulomb efficiency is greater than 90%.
Citation Information
Patent Citations
Method for flexibly regulating and controlling hard carbon negative electrode of lignite-based power type / capacity type sodium-ion battery and application of lignite-based power type / capacity type sodium-ion battery
CN116654893A
Method for preparing coke-based hard carbon through solvothermal-assisted low-temperature heat treatment
CN117776153A
Method for preparing battery by adopting coal physical-chemical combined deliming method
CN118026143A
Preparation method of bituminous coal-based hard carbon material by combining pre-pore-forming and high-temperature carbonization
CN118062827A
Coal-based hard carbon negative electrode material of sodium ion battery, preparation method and application thereof
CN113381013A